Precancerous Cervix in Human Immunodeficiency Virus Infected Women Thirty Years Old and above in Northern Uganda - Jonathan Izudi (Journal of Oncology, 2016)
Background. Little is known about precancerous cervical lesion (PCCL), the precursor of cervical cancer among Human Immunodeficiency (HIV) infected women in a postconflict setting of Northern Uganda. Objective. To establish factors associated with PCCL among HIV infected women above thirty years of age in a postconflict setting of Northern Uganda. Method. This retrospective cohort study used electronic data from 995 HIV-positive women that attended cervical cancer screening during June 2014 and December 2015. Data on social, sexual, obstetric, and gynecological factors was analyzed at 95% confidence level. Multivariate analysis determined factors independently associated with positive PCCL. Probability value less than 5% was considered significant. Results. Prevalence of PCCL was 3.0% (95% confidence interval (CI): 2.0–4.3). A positive PCCL was significantly associated with absence of sexually transmitted diseases (STDs) during clinic visits (adjusted odds ratio, aOR = 0.24; 95% confidence interval (CI): 0.09–0.64; P=0.004) and first pregnancy before the age of 20 years (aOR = 3.09; 95% CI: 1.21–7.89; P=0.018). Conclusion. The prevalence of PCCL was low in the postconflict setting of Northern Uganda. HIV-positive women presenting with STDs and those with first pregnancy before the age of 20 years were at increased risk of PCCL.